Analisis Kesulitan Belajar Matematika dan Upaya Menanganinya pada Siswa Kelas IV MI Gagaksipat 2 - Tisnawati, Tin; Mujahid, Kasori (Lembaga Yasin AlSys, 2024)
There are still many elementary school-age children who have learning difficulties in understanding the arithmetic operations of addition and subtraction which are presented in the form of story problems and the arithmetic operations of multiplication and division. The aim of this research is to determine the types of mathematics learning difficulties experienced by students, the factors that influence learning difficulties, and to reveal efforts that can be made to overcome mathematics learning difficulties in grade IV elementary school. This research method uses descriptive qualitative. The research subjects were 23 class IV students and class IV teachers. The data collection procedures used were observation, interviews, and documentation. The research results showed that 10 of the 23 students in class IV had difficulty learning mathematics. The types of learning difficulties for class IV students in mathematics learning at MI Gagaksipat 2 include difficulties understanding concepts, calculating skills, and solving problems. Factors that cause difficulties in learning mathematics come from internal and external factors. Internal factors originating from students include IQ or intelligence, students' attitudes toward learning mathematics, students' low learning motivation, suboptimal physical health, and students' poor sensory abilities. Meanwhile, external factors originating from outside students include the lack of variation in teacher teaching, the use of learning media that is not optimal, the infrastructure at school, and the family environment. Efforts to deal with mathematics learning difficulties can be made by students, teachers, or schools.